Vertical Land Movements and Sea Level Changes on South Georgia, South Atlantic Ocean: Results from 7 Years of Geodetic and Oceanographic Observations on a Remote Island - TEFERLE, Felix Norman; HUNEGNAW, Addisu; Hibbert, Angela; Williams, Simon D P; Woodworth, Philip L; Dalziel, Ian; Smalley, Robert Jr; Lawver, Laurence (2020)
South Georgia Island in the South Atlantic Ocean, is a small remote land mass that supports various ground-based instrumental observations (Global Navigation Satellite System (GNSS), tide gauge, meteorological and seismic) in an otherwise largely under sampled oceanic region. Moreover, the South Atlantic Ocean plays an important role in global ocean circulation, con-necting the deep thermohaline circulation of the North Atlantic and Indian Oceans, whilst also linking to the Antarctic Circumpolar Current in the South, where the lack of continental barriers allows a free exchange of water between the major ocean basins. Hence, South Georgia po-tentially lies within a region susceptible to climatic changes before these can be felt further afield. In 2013 and 2014 a total of five GNSS stations were installed covering the area of the main island (approximately 170 x 50 km) with two of those being located close to the King Edward Point (KEP) Research Station and the GLOSS tide gauge (ID 187). Furthermore, precise levelling campaigns in 2013, 2014, 2017 and 2020 supported the analysis of local ground instabilities near the tide gauge. Through these activities the tide gauge datum within the Permanent Ser-vice for Mean Sea Level (PSMSL) has been established, which in turn, makes the derived KEP mean sea level (MSL) record highly valuable for long-term studies and satellite altimetry cali-brations. In this study, we will present the vertical land movement estimates from seven years of GNSS observations, five precise levelling campaigns, and will discuss their impact on the sea level record from the KEP tide gauge and nearby satellite altimetry sea surface heights. Our results confirm uplift all over South Georgia Island while the area at KEP and particularly the jetty with tide gauge are subsiding relative to the rest of the island. Using this information we correct the MSL record for the vertical land movements and investigate its signals together with those from nearby satellite altimetry tracks. GSCG